STUDENT TEACHERS' VIEWS ON CURRICULUM REFORM DYNAMICS IN INDONESIA - Andromeda Valentino Sinaga (Al-Irsyad: Journal of Education Science, 2025)
The objective of this study is to examine the thoughts of Universitas Negeri Makassar student teacher regarding the dynamics of Indonesia's curriculum reforms. There was a survey conducted among 30 student teachers to identify their understanding of the curriculum, issues faced during its implementation, and recommendations for its improvement. The results show that although the students possess a good basic knowledge regarding curriculum theory, they are challenged by its Student Teachersin practice, particularly with regard to resource limitations and bureaucratic pressures. The students also recommended the provision of more practical training for prospective teachers, as well as facility and mentorship enhancements for the teachers in responding to the changes in the curriculum. This study provides information on how student teachers contribute perspectives that support the advancement of curriculum implementation in schools across Indonesia.